2013
DOI: 10.1016/j.rpor.2012.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant oral vs. infusional chemoradiotherapy on locally advanced rectal cancer: Prognostic factors

Abstract: Tumor and nodal downstaging, loco-regional response and a normal CEA level turned out to be important prognostic factors in locally advanced rectal cancer. Nodal downstaging and loco-regional response were higher in Group A. Those with tumor downstaging and loco-regional response from Group A had better OS. Adjuvant chemotherapy had no impact on survival except in those patients with loco-regional response who achieved a higher PFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…Treatment interruptions are another important indicator of quality that can have a marked effect on outcomes. 14 16 The usual causes of interruptions include machine malfunction or maintenance, toxicity, holidays, or unplanned quality control checks. In such cases, it is essential to have a protocol in place to compensate for the interruption.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment interruptions are another important indicator of quality that can have a marked effect on outcomes. 14 16 The usual causes of interruptions include machine malfunction or maintenance, toxicity, holidays, or unplanned quality control checks. In such cases, it is essential to have a protocol in place to compensate for the interruption.…”
Section: Discussionmentioning
confidence: 99%
“…The standard association for LCRCT is with 5-FU in continuous infusion, 14 but some evidence reported the equivalence of oral capecitabine. 27,28 The efficacy of the integration of oxaliplatin into the concurrent schedules is still controversial; some evidence suggests no benefit from such association due to increased toxicity without a significant improvement of pCR rates. That was basically reported by the STAR-01 29 and the ACCORD 12 30 trials, whereas the German trial (CAO/ARO/AIO-04) 31 reported on significant improvement for the oxaliplatin-based arm.…”
Section: Concomitant Chemotherapymentioning
confidence: 99%
“…Consiste en quimioterapia con base en fluoropirimidinas [16][17] , que se administra con dosis biológicas efectivas de radioterapia concomitante [14][15]18 . La efectividad se demuestra con el mayor tiempo libre de enfermedad, disminución del volumen tumoral, de la estadificación inicial y de la tasa de recaída local y regional, aunque no se ha demostrado aumento de la supervivencia global [12][13]19 .…”
Section: Introductionunclassified